Evaluation of basal heave factor of safety for jet-grouted excavation - Tan, Fiona Choon Yi (2015)
In braced excavation of clay, basal heave factor of safety is one of the major considerations for the engineers. To evaluate the basal heave factor of safety (FS), many conventional methods are proposed. The methods proposed by Terzaghi, and Bjerrum & Eide remain as two of the most commonly used ones. However, these two conventional methods disregard the stiffness of the wall (EI), width of excavation (B), as well as the depth of embedment (D). As these formulas are developed before the introduction of stiffer walls, the Finite Element Method (FEM) is used to evaluate the FS with greater precision. In this project, the FEM approach is used assuming plane strain two-dimensional models. PLAXIS 2D is the software used in the study to study the limitation of the conventional methods. A two-dimensional finite element parametric study was conducted with varying parameters such as the depth of embedment and wall stiffness. In addition, the project also focuses on the effects of jet grouting on FS. The thickness of the jet grout is also varied in the study to analyze the effects. A total of 48 cases are considered in this report. To draw comparison to the conventional methods, the results obtained are paralleled with the calculated ones. The differences in the FS and the relationship will also be discussed in the report. As the comparison is performed for the jet grouted cases, two proposed conventional methods are used. The result shows that FS increases with decreasing B, increasing D and EI and the presence of jet grout. Wall deflection is also significantly reduced with the installation of jet grout. As B increases, it is observed that the displacement in clay increased as well. The comparison of FS with conventional method shows that the bending failure method has the most conservative values. The discrepancy against PLAXIS results may be due to lack of consideration of certain excavation parameters. However, the equations are an estimate to obtain FS for jet grouted excavations. Since jet grouted cases are not considered in the conventional methods, these two proposed methods serve as good alternative methods. More data and investigation is required to improve the accuracy of the results.